Behaviorally efficient remedies: An experiment - Christoph Engel; Lars Freund (Max Planck Institute for Research on Collective Goods, 2017)
Under common law, the standard remedy for breach of contract is expectation damages. Under continental law, the standard is specific performance. The common law solution is ex post efficient. But is it also ex ante efficient? We use experimental methods to test whether knowing that non-fulfilment will only lead to damages deters mutually beneficial trade. The design excludes aversion against others willfully breaking their promises. We find that there is indeed less trade if specific performance is not guaranteed, provided the preference for the traded commodity is sufficiently pronounced.
Keywords: C91; D02; D03; D61; D62; D64; H23; K12; 330; remedies; breach of contract; specific performance; expectation damages; reliance damages; donation; experiment